Upregulation of Vitamin D Binding Protein (Gc-Globulin) Binding Sites During Neutrophil Activation from a Latent Reservoir in Azurophil Granules - DiMartino, Stephen J. (2006)
Vitamin D binding protein (DBP) is a multifunctional plasma transport protein that is also found on the surface of many cell types. Cell surface DBP significantly enhances chemotactic activity of complement (C) peptides C5a and C5a des Arg. However, both DBP binding and C5a chemotaxis enhancement can vary among neutrophil donors. To test if activation during cell purification is responsible for this variability, neutrophils were isolated using both standard and LPS-free protocols. Cells isolated by the LPS-free method had no DBP-enhanced chemotaxis to C5a or DBP binding to plasma membranes. Moreover, neutrophils treated with LPS bound more avidity to immobilized DBP than sham-treated cells. Subcellular fractionation of neutrophils (standard protocol) revealed a heavy plasma membrane (HM) band that contained components of light plasma membranes and all three granules. The HM band possessed most of the DBP binding activity (58%), and activation of cells with ionomycin greatly increased DBP binding to HM. Azurophil granules contained 33% of the total DBP binding sites and there was a highly significant positive correlation (r = 0.988) between release of the granule marker myeloperoxidase and DBP binding. These results indicate that fusion of granules with the plasma membrane forms HM that contains DBP binding sites.